Beyond probability-impact matrices in project risk management: A quantitative methodology for risk prioritisation. - Acebes Senovilla, Fernando; González-Varona, José Manuel; López-Paredes, Adolfo; Pajares Gutiérrez, Javier (Springer Nature, 2024)
The project managers who deal with risk management are often faced with the difficult task of determining the relative importance of the various sources of risk that affect the project. This prioritisation is crucial to direct management efforts to ensure higher project profit- ability. Risk matrices are widely recognised tools by academics and practitioners in various sectors to assess and rank risks according to their likelihood of occurrence and impact on project objectives. However, the existing literature highlights several limitations to use the risk matrix. In response to the weaknesses of its use, this paper proposes a novel approach for prioritising project risks. Monte Carlo Simulation (MCS) is used to perform a quantitative prioritisation of risks with the simulation software MCSimulRisk. Together with the definition of project activities, the simulation includes the identified risks by modelling their probability and impact on cost and duration. With this novel methodology, a quantitative assessment of the impact of each risk is provided, as measured by the effect that it would have on project duration and its total cost. This allows the differentiation of critical risks according to their impact on project duration, which may differ if cost is taken as a priority objective. This proposal is interesting for project managers because they will, on the one hand, know the absolute impact of each risk on their project duration and cost objectives and, on the other hand, be able to discriminate the impacts of each risk independently on the duration objective and the cost objective.
Los directores de proyectos que se ocupan de la gestión de riesgos a menudo se enfrentan a la difícil tarea de determinar la importancia relativa de las diversas fuentes de riesgo que afectan al proyecto. Esta priorización es crucial para dirigir los esfuerzos de gestión para garantizar una mayor rentabilidad del proyecto. Las matrices de riesgos son herramientas ampliamente reconocidas por académicos y profesionales de diversos sectores para evaluar y clasificar los riesgos según su probabilidad de ocurrencia y su impacto en los objetivos del proyecto. Sin embargo, la literatura existente destaca varias limitaciones para utilizar la matriz de riesgos. En respuesta a las debilidades de su uso, este artículo propone un enfoque novedoso para priorizar los riesgos del proyecto. La simulación Monte Carlo (MCS) se utiliza para realizar una priorización cuantitativa de riesgos con el software de simulación MCSimulRisk. Junto con la definición de las actividades del proyecto, la simulación incluye los riesgos identificados modelando su probabilidad e impacto en el costo y la duración. Con esta novedosa metodología se proporciona una evaluación cuantitativa del impacto de cada riesgo, medido por el efecto que tendría sobre la duración del proyecto y su coste total. Esto permite diferenciar los riesgos críticos según su impacto en la duración del proyecto, que puede diferir si se toma el coste como objetivo prioritario. Esta propuesta es interesante para los gestores de proyectos porque, por un lado, conocerán el impacto absoluto de cada riesgo en la duración de su proyecto y los objetivos de costes y, por otro lado, podrán discriminar los impactos de cada riesgo de forma independiente en la duración. objetivo y el objetivo de costes.
Keywords: Empresas - Gestión; Gestión del riesgo; Montecarlo, Método de; Modelos matemáticos; Métodos de simulación; Project management; Project risk; Risk management; Monte Carlo Simulation; Risk matrix